Soil Phosphorus Lability in a Sandy Soil in Response to Enhanced-Efficiency Phosphate Fertilizer for Sugarcane - de Oliveira, Clayton Luís Baravelli; Cassimiro, Juliana Bonfim; da Silva Lira, Maikon Vinicius; da Silva Boni, Ariele [UNESP]; de Lima Donato, Natália [UNESP]; Ribeiro, Igor Virgílio [UNESP]; dos Anjos Reis Junior, Roberto [UNESP]; Teles, Ana Paula Bettoni; Pavinato, Paulo Sérgio; Moreira, Adônis; Heinrichs, Reges [UNESP] (Taylor & Francis, 2025)
The high rate of phosphorus (P) fixation in tropical soils requires strategies that mitigate the effects of P immobilization by improving the efficiency of phosphate fertilization. The objective of this study was to evaluate the efficiency and residual effect of two sources of fertilizer (monoammonium phosphate–MAP-C and MAP coated with ‘Policote’ - MAP+P) on the lability of P in the soil and the nutritional status of sugarcane. The evaluations were carried out in two growing seasons (2018–2019 and 2019–2020). The experiment was arranged in randomized blocks, with four replicates. Treatments were organized in a factorial design (2 × 4) +1, with two P sources (MAP-C and MAP+P) under four rates (20, 40, 60, and 80 kg ha−1 P2O5) and a c ontrol treatment (without P2O5). Results indicate positive effects of MAP+P, the P levels in the labile fraction increase, while MAP-C induced increases in the labile organic fraction. However, this difference in the organic fraction is not repeated in the moderately labile fraction, where levels are higher in response to MAP+P. In response to MAP-C, the inorganic fraction, non-labile fraction, and total P increased, with no significant differences between treatments. The nutritional status of the crop is not affected by phosphate fertiization.
Keywords: P fractionation; phosphate polymers; Policote; S. officinarum